PENINGKATAN PRODUKSI PADI DI LAHAN LEBAK SEBAGAI ALTERNATIF DALAM PENGEMBANGAN LAHAN PERTANIAN KE LUAR PULAU JAWA - Djamhari, Sudaryanto (Jurnal Sains dan Teknologi Indonesia, 2009)
The rice production in Indonesia is not balance with the population rate. Thiscondition is caiseb by the productive agriculture land is coverted into housing area,industries/factories, roads, etc. The “Rawa Lebak” has a high potential to bedeveloped become productive agricultural land. But, there are severval constrainswhich have to be overcome, that is the source of water, where where in the dryseason there are drought and in the rainy season there are fload, the land is notfertile, and produtivity is low. Ogan Komering Ilir (OKI) District have “ Rawa Lebak”land area to a high of 164,034 hectars. In not deep and middle “rawa lebak” typeshave high potensial to be developed irrigation agricultural land trough technologyapplication in water management ang cultivation which can increase theagricultural index to 3 times anually and rice production reach to a high of 7,00tons/ha (dry reap). Therefore, “rawa lebak” can be used as alternative in theagriculture developmen outside Jawa.